Final report on VAMAS round‐robin study to evaluate a correction method for saturation effects in DSIMS. (17th April 2015) - Takano, Akio; Nonaka, Hidehiko; Homma, Yoshikazu; Tomita, Mitsuhiro; Murase, Atsushi; Hayashi, Syunichi; Barozzi, Mario; Kim, Kyung Joon; Sykes, David; Simons, David; Bennett, Joe; Magee, Charles W.
<x xml:space="preserve">Abstract</x> A Versailles Project on Advanced Materials and Standards round robin test (RRT) has been conducted to evaluate the linearity of the instrumental intensity scale and correction method using an approximation intermediate extended dead time model with parameters derived from two different isotope depth profiles. Nine organizations in five countries participated. An arsenic‐implanted silicon wafer and a film of BN diffused into a Si wafer were supplied by the National Institute of Advanced Industrial Science and Technology along with instructions for the RRT. The instruments used to analyze 103(AsSi)− and 105(AsSi)− from arsenic‐implanted samples were five quadrupole‐type SIMS and four magnetic‐sector type SIMS. The instruments used to analyze 10B+ and 11B+ from the BN‐diffused samples were three quadrupole‐type SIMS, four magnetic‐sector type SIMS, and one time‐of‐flight type SIMS. We validated the usefulness of the approximation intermediate extended dead time model to correct saturated intensities for all SIMS in this RRT. The optimum extension parameter ρ tends to be affected by the ratio of the maximum reliable intensity to the maximum intensity in raw profiles. From the ratio, ρ may be predicted when the intensity reaches full saturation. On the other hand, ρ is also affected by lateral non‐uniformity of intensity. In practice, because the maximum intensity does not reach full saturation and the intensity is not laterally uniform, ρ is likely to be smaller than its predicted value. Copyright © 2015 John Wiley & Sons, Ltd.